DEMOKRATISASI PENDIDIKAN DALAM PENDIDIKAN ISLAM - Fathorrahman (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
Educational democracy is a democracy that provides equal educational opportunities to all people, regardless of race (ethnicity), beliefs, color and social status. The principles of democracy can be implemented in the Islamic education system because basically Islam gives freedom to individuals (students) to develop the values of nature that are in themselves in aligning with the times. The democratization of education in Islamic education is reflected in aspects: First: Monotheism: a paradigm of liberation. Second, Shura: a vehicle for openness. Third, Al-Adlu: a classless society. Fourth, Amar Makruf Nahi Mungkar: monotheistic, doing good deeds, being cautious and ulul albab. Fifth, Tawassut Principle: principle of moderation. Sixth, the obligations and human rights in the development of science.